2016
DOI: 10.1038/srep29823
|View full text |Cite
|
Sign up to set email alerts
|

Systematic investigation of transcription factors critical in the protection against cerebral ischemia by Danhong injection

Abstract: Systematic investigations of complex pathological cascades during ischemic brain injury help to elucidate novel therapeutic targets against cerebral ischemia. Although some transcription factors (TFs) involved in cerebral ischemia, systematic surveys of their changes during ischemic brain injury have not been reported. Moreover, some multi-target agents effectively protected against ischemic stroke, but their mechanisms, especially the targets of TFs, are still unclear. Therefore, a comprehensive approach by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 57 publications
(75 reference statements)
0
28
0
Order By: Relevance
“…This protection may be achieved through the regulation of amino acid metabolites and metabolic pathways [84,85]. A study of transcription factors in cerebral ischemic injury showed that eight transcription factors, such as cyclic AMP-dependent transcription factor 1 (ATF1) and pre-B cell leukemia transcription factor 1 (PBX1) are target transcription factors responsible for DHI-mediated protection against cerebral ischemic injury [86]. DHI also exerts a neuroprotective action in a rat model of cerebral I/R injury by preserving the blood-brain barrier, and reversing neutrophil infiltration [87].…”
Section: Experimental Studies and Molecular Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…This protection may be achieved through the regulation of amino acid metabolites and metabolic pathways [84,85]. A study of transcription factors in cerebral ischemic injury showed that eight transcription factors, such as cyclic AMP-dependent transcription factor 1 (ATF1) and pre-B cell leukemia transcription factor 1 (PBX1) are target transcription factors responsible for DHI-mediated protection against cerebral ischemic injury [86]. DHI also exerts a neuroprotective action in a rat model of cerebral I/R injury by preserving the blood-brain barrier, and reversing neutrophil infiltration [87].…”
Section: Experimental Studies and Molecular Mechanismsmentioning
confidence: 99%
“…DHI is a composite formula of two eminent Chinese herbal medicine-Salviae Miltiorrhizae (Dan Shen) and Flos Carthami (Hong Hua). Compared with single-target western medicine, DHI is a multi-component and multi-target medicinal preparation, which indicates that DHI may have a wider range of clinical applications [10,86,106].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Dynamic changes of proteins in hiPS-C cells during cardiac dysfunction were investigated by collecting cells after exposure to ET-1 for 12, 24, 48, and 72 h for high-throughput proteomic profiling. An accurate iBAQ-based approach was used (24,31,37), and the iBAQ value of each protein was normalized to the total iBAQ value for all the identified proteins to avoid possible experimental variations (24,31). Three individual samples were analyzed in each group, and dynamic changes were precisely identified by statistical analyses of the measured protein amounts from each individual sample (24).…”
Section: Dynamic Changes Of Proteins In Et-1-induced Dysfunctional Himentioning
confidence: 99%
“…Because of the superior comprehensiveness of proteomics and their powerful quantitative ability (27,28), this approach offers an opportunity to identify the changes of the signatures and biomarkers when perturbed with a drug. Next, after a systems-level explanation of the interactions of multiple drug components by a network pharmacology-based (29)(30)(31) approach and final validation in HF rat models, the signature biomarkers regulated by the multicomponent drugs against HF can be confirmed and the corresponding precise clinical localization deduced. The newly developed approach was then applied to a multicomponent conventional drug for cardiac disease, YiXinShu (YXS), a sheng mai san-based TCM formula (32)(33)(34).…”
mentioning
confidence: 99%
“…contributed equally to this work. Pharmacology 2018;102:154-160 DOI: 10.1159/000491020 [1,2], is used extensively in the treatment of cardio-cerebrovascular diseases with the functions of promoting blood circulation to remove blood stasis, and dredging the channels. Its various effective ingredients, including protocatechuic aldehyde (PAL) and hydroxysafflor yellow A (HSYA), have been proved to possess a positive effect on anti-thrombotics, regulation of lipid metabolism, atherosclerosis, and anti-oxidants [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%